ASTP: MODEL PEMBELAJARAN BAHASA ASING BAGI MILITER - Nasution, A. Sayuti Anshari (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
The United States Army during the Second World War stunned the education world with their foreign language teaching experience. Their program that is called â€œThe Army Specialized Training Programâ€ (ASTP) was able to successfully train many participants with a very high success rate. Dr. Hamada Ibrahim, a professor in foreign languages at Cairo University, Egypt, described the â€œASTPâ€ as the most immense and successful program of learning foreign language in the history. The US Army foreign language program encompasses the background for the emergence of this program, a general picture of the program, the teaching subjects as well as the teaching techniques.